2022
DOI: 10.1103/physrevmaterials.6.014008
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magneto-optical properties of ferromagnetic monolayer CrBr3 : A first-principles GW and GW plus Bethe-Salpeter equation study

Abstract: The discovery of atomically thin two-dimensional (2D) magnetic semiconductors has triggered enormous research interest recently. In this work, we use first-principles many-body perturbation theory to study a prototypical 2D ferromagnetic semiconductor, monolayer chromium tribromide (CrBr3). With broken time-reversal symmetry, spin-orbit coupling, and excitonic effects included through the full-spinor GW and GW plus Bethe-Salpeter equation (GW-BSE) methods, we compute the frequency-dependent dielectric function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 79 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…To further reveal the influence of different materials on valley polarization, their spin-projected band structures are extracted individually and plotted in Figure c–e. According to crystal field theory, since the Cr 3+ ions are located in an octahedral environment coordinated by six Br – ions in a CrBr 3 crystal, as shown in Figure c, the Cr-3d orbitals are split into three low-lying t 2g and two high-lying e g orbitals. , The e g orbitals constitute the majority-spin, and the spin direction is the same as the magnetization direction in CrBr 3 material . As for WS 2 , as shown in Figure d, its band structures at K and K′ valleys are almost the same as that of the individual WS 2 monolayer (see Figure S7 in the Supporting Information) because of its weak coupling with the CrBr 3 crystal .…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…To further reveal the influence of different materials on valley polarization, their spin-projected band structures are extracted individually and plotted in Figure c–e. According to crystal field theory, since the Cr 3+ ions are located in an octahedral environment coordinated by six Br – ions in a CrBr 3 crystal, as shown in Figure c, the Cr-3d orbitals are split into three low-lying t 2g and two high-lying e g orbitals. , The e g orbitals constitute the majority-spin, and the spin direction is the same as the magnetization direction in CrBr 3 material . As for WS 2 , as shown in Figure d, its band structures at K and K′ valleys are almost the same as that of the individual WS 2 monolayer (see Figure S7 in the Supporting Information) because of its weak coupling with the CrBr 3 crystal .…”
mentioning
confidence: 82%
“…According to crystal field theory, since the Cr 3+ ions are located in an octahedral environment coordinated by six Br − ions in a CrBr 3 crystal, as shown in Figure 4c, the Cr-3d orbitals are split into three lowlying t 2g and two high-lying e g orbitals. 37,38 The e g orbitals constitute the majority-spin, and the spin direction is the same as the magnetization direction in CrBr 3 material. 19 As for WS 2 , as shown in Figure 4d, its band structures at K and K′ valleys are almost the same as that of the individual WS 2 monolayer (see Figure S7 in the Supporting Information) because of its weak coupling with the CrBr 3 crystal.…”
mentioning
confidence: 99%
“…Grzeszczyk et al revealed such dramatic differences in the exciton-magnetization coupling between the two systems by analyzing the exciton wave functions in band-, orbital-, spin-basis and in real space. The authors also noted that a part of the essential conclusions were different if a nonself-consistent (single-shot) GW theory , was used instead of a fully self-consistent theory. A self-consistent, parameter free, many-body perturbative approach appears to be more important in the “Frenkel” limit where the electron and hole parts of the excitonic wave function get delocalized in the band-basis over several valence and conduction bands (Figure ) (which includes both p and d characters and contain spins of both kinds), in strong contrast to Wannier-Mott limit where a reasonable description of the electron and hole wave functions from the conduction band bottom and valence band top is sufficient to describe the excitons reliably.…”
Section: Materials Physics and Electronic Structurementioning
confidence: 99%
“…Another recent study activates the dark excitons in CrCl 3 by forming heterostructures with WSe 2 . Moreover, additional studies show that the direct or indirect nature of the electronic band gaps do change going from bulk to single layer. This can have important consequences in tuning the brightness of the excitons across different numbers of layers.…”
Section: Outlook and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation